Divergent CD4+ T-cell profiles are associated with anti-HLA alloimmunization status in platelet-transfused AML patients - Khelfa, Mehdi; Leclerc, Mathieu; Kerbrat, Stéphane; Boudjemai, Yakout Nait Sidenas; Benchouaia, Médine; Neyrinck-Leglantier, Déborah; Cagnet, Léonie; Berradhia, Lylia; Tamagne, Marie; Croisille, Laure; Pirenne, France; Maury, Sébastien; et al. (Frontiers in Immunology, 2023)
Acute myeloid leukemia (AML) is one of the commonest hematologic disorders. Due to the high frequency of disease-or treatment-related thrombocytopenia, AML requires treatment with multiple platelet transfusions, which can trigger a humoral response directed against platelets. Some, but not all, AML patients develop an anti-HLA immune response after multiple transfusions. We therefore hypothesized that different immune activation profiles might be associated with anti-HLA alloimmunization status. We tested this hypothesis, by analyzing CD4+ T lymphocyte (TL) subsets and their immune control molecules. A comparison of immunological status between anti-HLA alloimmunized and nonalloimmunized AML patients identified differences in the phenotype and function of CD4+ TLs. CD4+ TLs from alloimmunized patients displayed features of immune activation, with higher levels of CD40 and OX40 than the cells of healthy donors. However, the most notable differences were observed in non-alloimmunized patients. These patients had lower levels of CD40 and OX40 than alloimmunized patients and higher levels of PD1. Moreover, the Treg compartment of non-alloimmunized patients was larger and more functional than that in alloimmunized patients. These results were supported by a multi-omics analysis of immune response molecules in conventional CD4+ TLs, Tfh circulating cells, and Tregs. Our results thus reveal divergent CD4+ TL characteristics correlated with anti-HLA alloimmunization status in transfused AML patients. These differences, characterizing CD4+ TLs independently of any specific antigen, should be taken into account when considering the immune responses of patients to infections, vaccinations, or transplantations.